Improved enrichment and analysis of heterocyclic aromatic amines in thermally processed foods by magnetic solid phase extraction combined with HPLC-MS/MS. (July 2022) - Feng, Yanmei; Xu, Ying; Li, Wenrui; Chen, Shasha; Su, Zhuoqun; Xi, Lingyi; Li, Guoliang
Abstract: Heterocyclic aromatic amines (HAAs) are potently mutagenic and carcinogenic compounds formed during thermal processing foods. However, due to the complexity of the food matrix and trace levels of HAAs, rapid and effective detection of HAAs has always been a challenge. In this study, novel magnetic covalent organic polymers (Fe3 O4 @COP) were synthesized as adsorbents for effectively and rapidly enriching HAAs. Meanwhile, the proposed materials were endowed with good selectivity and superior purification ability to effectively alleviate the matrix effect interference of complex food samples. Then, a reliable and sensitive method was developed for the determination of HAAs by magnetic solid-phase extraction combined with HPLC-MS/MS. The established method displayed good linearity (R 2  ≥ 0.9984) with the satisfactory limits of detection (0.020–0.375 μg kg −1 ) and recoveries (82.0–109.5%). Further, the developed method was applied to determine HAAs in different types of thermally processed meat products, showing excellent applicability. Results showed that different thermal processing methods promoted the generation of HAAs in the order of frying, roasting and grilling, and boiling. Norharman and Harman were the predominant HAAs in thermally processed meat products. Highlights: Novel magnetic Fe3 O4 @COP was prepared for enrichment of HAAs in foodstuffs. A facile method was developed to detect six HAAs by MSPE coupled with HPLC-MS/MS. Method validation indicated the proposed method was accurate and reliable. Method was successfully applied to detect HAAs in actual thermally processed foods. The concentration characteristics of HAAs in thermally processed meats were explored.